Brand repositioning of Egypt's Muslim brotherhood: do you see what I see, views from the female electorate?. (4th May 2020) - McPherson, Mark; Ismail, Monia Mohsen
The paper explores brand-repositioning of the MB and FJP, as viewed by Egypt's female voters during 2010/2011 Presidential elections. Five areas of brand-repositioning were discussed. Multiple sources of evidence were used, namely commentary from 46 female respondents: 1) 22 face-to-face interviews; 2) four focus groups by age containing six respondents within each; 3) projective techniques - drawing and sentence completion. Judgemental/snowballing sampling were employed. Data was analysed via content analysis. Gaps exists between how the MB perceive their image and how respondents view such image. Respondents displayed concern about female expectations in the future; felt that pre-revolution the MB were, 'repressed', during were 'heroes'. Post, their image declined because they became authoritarian and curtailed women and minority rights. Insights are offered into the views and emotions held by Egypt's female voters towards both parties. Such insights expose a gap in the literature pertaining to Egypt's female electorate.